Product Design for Mass Individualisation for Industrial Application - Sikhwal,RK; Childs,PRN (IEEE, 2018)
In the last few years, a demand for renewed product personalisation to satisfy the exact need of the customers has been observed in some markets. As opposed to customisation, which put emphasis on the satisfaction of explicit needs of a defined market segment, individualisation aims at satisfying the specific needs of a customer. Product design for Mass Individualisation (MI) is a new product design paradigm that comprises an open hardware platform and multiple modules that are integrated with the platform, as per end-users’ choice. This paper identifies key areas and components which need to be focused to realise this approach and convert it into an industrial practice by an explorative study of existing product design and customisation approaches. A questionnaire survey has been conducted and results are presented for the industrial implication and insights on this approach. The findings clearly show that MI provides most individualised and technologically advanced product.